2015
DOI: 10.1002/2015ja021082
|View full text |Cite
|
Sign up to set email alerts
|

How to find magnetic nulls and reconstruct field topology with MMS data?

Abstract: In this study, we apply a new method—the first‐order Taylor expansion (FOTE)—to find magnetic nulls and reconstruct magnetic field topology, in order to use it with the data from the forthcoming MMS mission. We compare this method with the previously used Poincare index (PI), and find that they are generally consistent, except that the PI method can only find a null inside the spacecraft (SC) tetrahedron, while the FOTE method can find a null both inside and outside the tetrahedron and also deduce its drift ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
180
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 123 publications
(190 citation statements)
references
References 30 publications
3
180
0
Order By: Relevance
“…The recent MMS mission can readily satisfy the first criterion: from September 2015 to electron agyrotropy ( P 2 xy þ P 2 xz þ P 2 Swisdak, 2016) is prominent (Webster et al, 2018), meaning that MMS was located inside the EDRs. This technique is able to accurately resolve the magnetic null position and reconstruct the magnetic topology around the spacecraft tetrahedron and is particularly useful for the spacecraft mission with small separation, like MMS (Fu et al, 2015). This technique is able to accurately resolve the magnetic null position and reconstruct the magnetic topology around the spacecraft tetrahedron and is particularly useful for the spacecraft mission with small separation, like MMS (Fu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The recent MMS mission can readily satisfy the first criterion: from September 2015 to electron agyrotropy ( P 2 xy þ P 2 xz þ P 2 Swisdak, 2016) is prominent (Webster et al, 2018), meaning that MMS was located inside the EDRs. This technique is able to accurately resolve the magnetic null position and reconstruct the magnetic topology around the spacecraft tetrahedron and is particularly useful for the spacecraft mission with small separation, like MMS (Fu et al, 2015). This technique is able to accurately resolve the magnetic null position and reconstruct the magnetic topology around the spacecraft tetrahedron and is particularly useful for the spacecraft mission with small separation, like MMS (Fu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The reported magnetic islands were observed from shock surface to the vicinity of the magnetopause, had a spatial size of a few tens of ion inertial length in the magnetosheath, and were characterized by a density depletion and magnetic field compression [Karimabadi et al, 2014, Figures 6, 9, and 13]. In spacecraft data, distinguishing between magnetic islands and flux ropes is not obvious (magnetic islands can indeed be seen as the 2-D version of 3-D flux ropes [e.g., Fu et al, 2015Fu et al, , 2016). In spacecraft data, distinguishing between magnetic islands and flux ropes is not obvious (magnetic islands can indeed be seen as the 2-D version of 3-D flux ropes [e.g., Fu et al, 2015Fu et al, , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The topological degree equals the sum of the numbers of positive and negative nulls inside a closed volume of space. Its drawbacks are the inability to detect nulls outside this closed volume of space (e.g., a tetrahedron formed by four spacecraft)and theimpossibility of recovering the exact number and positions of the nulls enclosed (Fu et al 2015).…”
Section: Location and Classification Of Nullsmentioning
confidence: 99%
“…The interest to the magnetic nulls is growing in the community. Most recently Fu et al (2015) suggested a new method of null point identification based on the first-order Taylor expansion of themagnetic field (FOTE). In distinction from the widely adopted methods (Greene 1992;Haynes & Parnell 2007), FOTE could locate nulls even outside the region of space enclosed by the spacecraft.…”
Section: Introductionmentioning
confidence: 99%